Dietary baked milk accelerates the resolution of cow’s milk allergy in children - Kim, Jennifer S.; Nowak-Węgrzyn, Anna; Sicherer, Scott H.; Noone, Sally; Moshier, Erin L.; Sampson, Hugh A. (Journal of allergy and clinical immunology, 2011)
The majority (approximately 75%) of children with cow’s milk allergy tolerate extensively heated (baked) milk products. Long-term effects of inclusion of dietary baked milk have not been reported. We report on the outcomes of children who incorporated baked milk products into their diets. Children evaluated for tolerance to baked milk (muffin) underwent sequential food challenges to baked cheese (pizza) followed by unheated milk. Immunologic parameters were measured at challenge visits. The comparison group was matched to active subjects (by using age, sex, and baseline milk-specific IgE levels) to evaluate the natural history of development of tolerance. Over a median of 37 months (range, 8-75 months), 88 children underwent challenges at varying intervals (range, 6-54 months). Among 65 subjects initially tolerant to baked milk, 39 (60%) now tolerate unheated milk, 18 (28%) tolerate baked milk/baked cheese, and 8 (12%) chose to avoid milk strictly. Among the baked milk–reactive subgroup (n = 23), 2 (9%) tolerate unheated milk, and 3 (13%) tolerate baked milk/baked cheese, whereas the majority (78%) avoid milk strictly. Subjects who were initially tolerant to baked milk were 28 times more likely to become unheated milk tolerant compared with baked milk–reactive subjects ( P < .001). Subjects who incorporated dietary baked milk were 16 times more likely than the comparison group to become unheated milk tolerant ( P < .001). Median casein IgG 4 levels in the baked milk–tolerant group increased significantly ( P < .001); median milk IgE values did not change significantly. Tolerance of baked milk is a marker of transient IgE-mediated cow’s milk allergy, whereas reactivity to baked milk portends a more persistent phenotype. The addition of baked milk to the diet of children tolerating such foods appears to accelerate the development of unheated milk tolerance compared with strict avoidance.